2006
DOI: 10.1007/s10165-006-0456-8
|View full text |Cite
|
Sign up to set email alerts
|

A case of idiopathic portal hypertension associated with rheumatoid arthritis

Abstract: A 53-year-old woman who had been diagnosed with rheumatoid arthritis was found to have thrombocytopenia, splenomegaly, and gastric varices. She was diagnosed as having idiopathic portal hypertension on the basis of liver biopsy and angiography. Treatment with prednisolone was not sufficiently effective for thrombocytopenia. After transabdominal devascularization with splenectomy, thrombocytopenia subsided and gastric varices disappeared. In this case, the autoimmune mechanism as well as hypersplenism was suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Recent studies have shown that IPH is associated with many autoimmune diseases, such as systemic sclerosis 15 , systemic lupus erythaematosus 16 and rheumatoid arthritis 9 . These results, combined with our own, indicate that IPH may be secondary to inflammation of connective tissue and vasculitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that IPH is associated with many autoimmune diseases, such as systemic sclerosis 15 , systemic lupus erythaematosus 16 and rheumatoid arthritis 9 . These results, combined with our own, indicate that IPH may be secondary to inflammation of connective tissue and vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of IPH is complicated. The most common cause is certain kinds of drugs, such as thiopurine 1-3 and arsenical salts 4,5 , and other causes include a series of autoimmune diseases, such as Hashimoto's thyroiditis 6,7 , noninfectious hepatitis 7,8 and rheumatoid arthritis 9 . Similar to cirrhosis, IPH can also lead to hepatic failure, splenomegaly, variceal bleeding and ascites 10 , making it difficult to differentiate IPH from cirrhosis.…”
mentioning
confidence: 99%
“…Other rare conditions, including NRH, idiopathic portal hypertension, and spontaneous hepatic rupture secondary to vasculitis, have also been reported. 49 , 57 60 , 61 RA is generally defined as the combined presence of arthropathy and the rheumatoid factor (RF). However, similarity in extrahepatic manifestations of primary liver disorders might be confusing.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…An accompanying autoimmune disease (e. g. systemic lupus erythematosus, rheumatoid arthritis) is not uncommon in IPH patients [10,12]. Babbs et al report a patient with IPH who developed IgA nephropathy and a nephrotic syndrome [17].…”
Section: Case Presentationmentioning
confidence: 99%